2021
DOI: 10.1017/s1355617720001393
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Stroke: Computer-based Assessment Uncovers Non-Lateralized and Contralesional Visuoattentive Deficits

Abstract: Objective: Patients with unilateral stroke commonly show hemispatial neglect or milder contralesional visuoattentive deficits, but spatially non-lateralized visuoattentive deficits have also been reported. The aim of the present study was to compare spatially lateralized (i.e., contralesional) and non-lateralized (i.e., general) visuoattentive deficits in left and right hemisphere stroke patients. Method: Participants included 40 patients with chronic unilateral stroke in either the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…As previously described (Villarreal et al, 2020(Villarreal et al, , 2021, LH patients in our sample showed no spatial bias in visual attention, and RH patients showed only subtle neglect, which was not evident in the traditional cancellation task, the Bells Test. Therefore, in the present study, we used more sophisticated approaches for data analysis to potentially increase the sensitivity of the new cancellation task.…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…As previously described (Villarreal et al, 2020(Villarreal et al, , 2021, LH patients in our sample showed no spatial bias in visual attention, and RH patients showed only subtle neglect, which was not evident in the traditional cancellation task, the Bells Test. Therefore, in the present study, we used more sophisticated approaches for data analysis to potentially increase the sensitivity of the new cancellation task.…”
Section: Methodssupporting
confidence: 81%
“…As the RH patients' visuospatial attention deficits were only subtle, they became more clearly evident in bilateral than unilateral trials, i.e., as an extinction. While the phenomenon was seen here in the dual-tasks, RH patients also showed extinction in the single task in our previous study (Villarreal et al, 2021). Our first study (Villarreal et al, 2020) demonstrated that the RH patients (but not LH patients) showed statistically reliable contralesional omissions for unilateral targets as well, in two different dual-tasks.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Instead, USN+ patients’ total score was significantly lower than the controls’ in the multiple task variant, showing both lateralized and non-lateralized attention deficits. General inattention has been shown to co-occur with USN ( Ting et al, 2011 , Nurmi et al, 2018 , Villarreal et al, 2021 ). The difference between the score results in single and multiple tasks may also partly relate to the practice effect: a single task was always performed before multiple task.…”
Section: Discussionmentioning
confidence: 99%